• Ashy98
A. Given the equation 4x + 7 = 3(2x − 5), solve for the variable. Explain each step and justify your process. B. Sam solved a similar equation below. Is Sam's solution correct? Explain why or why not. 5x − 1 = 2(x + 4) 5x − 1 = 2x + 8 7x − 1 = 8 7x = 7 x = 1
  • Stacey Warren - Expert
Hey! We 've verified this expert answer for you, click below to unlock the details :)
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
  • katieb
I got my questions answered at in under 10 minutes. Go to now for free help!
  • tkhunny
Well, do it? What's preventing you from taking the first step?
  • Ashy98
Part A: 4x + 7 = 6x - 15 4x - 6x = 15 - 7 (Collect all like terms) -2x = 8 (divide both side by -2) x = -4
  • anonymous
Part A: x=11 4x+7=6x-15 [Distributive Property] 4x=6x-22 [Subtract 7 from both sides] -2x=-22 [Subtract 6x from both sides] x=11 [Divide Both sides by -2] Part B: Sam is incorrect Sam got the first step right but he messed up the second, he added 2x on both sides to get 7x on the left when in fact he should've subtracted 2x to give him 3x on both sides

Looking for something else?

Not the answer you are looking for? Search for more explanations.